Strategi Pemberdayaan Usaha Kecil Menuju Kemandirian Usaha dengan Menerapkan Manajemen Profesional - Sukirman, Sukirman; Indaryani, Mamik (Jurnal Ilmu Manajemen, 2014)
This research aimed to studied phenomena which influence micro business difficulty therefore needed to follow up by empirical study, it was: first, study about organization and marketing, study of business strategy, human resources, which could influence the process of created such micro business to made independent, strong and healthy business. Both method and research technique used was such combination among literature study, respondent observation, interview method with micro business object,product user and small business group structurally and indept interview). Analysis within this research was used descriptive analysis to studied presence both organization and marketing, stragegical research, human resource stakeholder and bechmarking examinations. Identified and studiedpresence variable was implemented by using SPSS program support. Qualitative analysis used by focus group discussion (FGD) between researcher and micro business manager. Based on examination result was showed that micro business still have difficulty to manage organization, marketing, business strategy and human resource management. Thiscondition occured as a consequence from hereditary management, inability to accessing both knowledge and technology development, and culture environment rooted therefore difficult to implement alteration. Thereforeneeded Local Government's role to utilize micro business to develop become independent business, health, strong and professional.